Protein Kinase D1 Signaling in Angiogenic Gene Expression and VEGF-Mediated Angiogenesis - Ren, Bin (Frontiers in Cell and Developmental Biology, 2016)
Protein kinase D 1 (PKD-1) is a signaling kinase important in fundamental cell functions including migration, proliferation and differentiation. PKD-1 is also a key regulator of gene expression and angiogenesis that is essential for cardiovascular development and tumor progression. Further understanding molecular aspects of PKD-1 signaling in the regulation of angiogenesis may have translational implications in obesity, cardiovascular disease and cancer. The author will summarize and provide the insights into molecular mechanisms by which PKD-1 regulates transcriptional expression of angiogenic genes, focusing on the transcriptional regulation of CD36 by PKD-1-FoxO1 signaling axis along with the potential implications of this axis in arterial differentiation and morphogenesis. He will also discuss a new concept of dynamic balance between proangiogenic and antiangiogenic signaling in determining angiogenic switch, and stress how PKD-1 signaling regulates VEGF signaling-mediated angiogenesis.